Gamification of In-House Training : Potential of utilizing gamification in sales force training - Saramola, Janne (My University, 2024)
This research explores the possible benefits of utilizing gamification in sales training. The benefits are presented through conducting a literature review as well as by interviewing professionals that are relevant to the research topic. The literature review provides the theoretical background as it explores the concept of gamification, current state of sales training and summarizes previous studies that have been done on the use of gamification in organizations. Expert interviews provide depth to the study and act as the empirical section of this thesis. Interviews provide insight to how gamification and sales training could be combined. The findings of the study provide promising results into the possible benefits of gamification in terms of use in sales training. The results illustrate the problems with sales training, but also paint a picture of the potential fixes that could be done by introducing game elements into sales training. Improved motivation, engagement, and a better memory trace, combined with improved team spirit are only some of the benefits that can be achieved by utilizing gamification in sales training. This study also elaborates on why sales professionals are a good target group for gamified trainings due to the competitiveness that is found in most sales professionals. These results are significant to organizations that consider freshening or changing the training of their sales professionals. This research provides these organizations with information and insight into why they should consider utilizing game elements, and why sales professionals are ideal candidates and target group for such training. This research area has not been a subject to previous research, which gives importance to these findings. However, the study could benefit from further research as it could provide further findings or additional details supporting those presented in this thesis.

Tämä tutkimus tutkii mahdollisia hyötyjä, joita pelillistämistämisestä voi saada myyntikoulutukseen. Hyötyjä käsitellään kirjallisuuskatsauksen ja asiantuntijahaastatteluiden avulla. Sekä kirjallisuuskatsaus että asiantuntijahaastattelut ovat relevantteja tutkimusaiheen kannalta. Kirjallisuuskatsaus luo tutkimuksen teoreettisen pohjan tutkien pelillistämistä ja myyntikoulutuksen nykytilaa. Kirjallisuuskatsauksessa myös tiivistetään aiempia tutkimuksia, joiden aihe liittyy pelillistämiseen organisaatioissa. Haastatteluista tutkimus saa näkemystä siitä, miten pelillistäminen ja myyntikoulutus vosiivat mahdollisesti täydentää toisiaan. Tutkimuksen tulokset esittävät lupaavia tuloksia pelillistämisen hyödyistä myyntikoulutuksessa. Tulokset havainnollistavat ongelmia, joita myyntikoulutuksessa tällä hetkellä on, löytäen niihin mahdollisia ratkaisuja ja parannuskeinoja pelielementtien implementoinnista myyntikoulutukseen. Parantuneet motivaatio ja sitoutuminen sekä parempi muistijälki ja opitun muistaminen, yhdistettynä kohonneeseen tiimihenkeen ovat vain esimerkkejä hyödyistä, joita voidaan saavuttaa pelillistämisen ja pelielementtien käyttämisellä myyntikoulutuksessa. Tämä tutkimus esittää myös, miksi myyntiammattilaiset ovat erinomainen kohderyhmä pelillistetylle myyntikoulutukselle. Tämä johtuu kilpailuvietistä, joka on yleistä monille myyjille. Tämän tutkimuksen tulokset ovat merkittäviä organisaatioille, jotka harkitsevat uudistavansa myyjien koulutusta. Tämä tutkimus tarjoaa tietoa ja näkemyksiä siitä, miksi pelielementtien hyödyntämistä kannattaa harkita, ja miksi myyjät ovat kyseiselle koulutusformaatille erinomainen kohderyhmä. Tätä tutkimusaluetta ei ole aiemmin juurikaan tutkittu, mikä korostaa näiden löydösten ja tutkimustulosten merkitystä. Tutkimus kuitenkin hyötyisi aiheeseen liittyvästä lisätutkimuksesta, sillä se voisi tuottaa lisätietoa tai tarkempia yksityiskohtia, jotka tukisivat tässä tutkimuksessa esitettyjä väitteitä ja tuloksia.
Keywords: Gamification, Sales training, game elements